The dynamics of alcohol and marijuana initiation: patterns and predictors of first use in adolescence - Rick Kosterman; J. David Hawkins; Jie Guo; Richard F. Catalano; Robert D. Abbott (2000)
This study, guided by the social development model, examined the dynamic patterns and predictors of alcohol and marijuana use onset.Survival analysis and complementary log-log regression were used to model hazard rates and etiology of initiation with time-varying covariates. The sample was derived from a longitudinal study of 808 youth interviewed annually from 10 to 16 years of age and at 18 years of age.Alcohol initiation rose steeply up to the age of 13 years and then increased more gradually; most participants had initiated by 13 years of age. Marijuana initiation showed a different pattern, with more participants initiating after the age of 13 years.This study showed that: (1) the risk of initiation spans the entire course of adolescent development; (2) young people exposed to others who use substances are at higher risk for early initiation; (3) proactive parents can help delay initiation; and (4) clear family standards and proactive family management are important in delaying alcohol and marijuana use, regardless of how closely bonded a child is to his or her mother.